2012
DOI: 10.1051/eas/1258035
|View full text |Cite
|
Sign up to set email alerts
|

Clathrate hydrates : ftir spectroscopy for astrophysical remote detection

Abstract: Abstract. Inclusion compounds made of a water ice network, clathrate hydrates, are investigated by infrared spectroscopy. Because they can trap important "guest" volatiles species, they may influence the equilibrium, exchange and flux of volatiles in many bodies of the solar system. Their spectroscopic behaviour at low temperature (10-200 K) are shown and the search for their signatures by comparison to solar system objects remote spectra are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Petuya et al [43] have shown that Raman spectroscopy can be quite useful in determining the extent of partitioning of a CO guest in a clathrate hydrate host lattice containing several different host sites. The FTIR spectroscopy studies of Dartois et al [40,44] regarding the possibility of astrophysical remote detection of clathrate hydrates on Pluto and Triton lead to the observation that the methane (CH 4 ) associated with these bodies was not encapsulated in clathrate hydrates. Raman and resonance Raman investigations of halogen clathrate hydrates are most helpful in elucidating host-guest interactions in these highly colored systems.…”
Section: Nmr Raman Infrared Spectroscopymentioning
confidence: 99%
“…Petuya et al [43] have shown that Raman spectroscopy can be quite useful in determining the extent of partitioning of a CO guest in a clathrate hydrate host lattice containing several different host sites. The FTIR spectroscopy studies of Dartois et al [40,44] regarding the possibility of astrophysical remote detection of clathrate hydrates on Pluto and Triton lead to the observation that the methane (CH 4 ) associated with these bodies was not encapsulated in clathrate hydrates. Raman and resonance Raman investigations of halogen clathrate hydrates are most helpful in elucidating host-guest interactions in these highly colored systems.…”
Section: Nmr Raman Infrared Spectroscopymentioning
confidence: 99%